2016
DOI: 10.1292/jvms.15-0545
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of <i>Encephalitozoon cuniculi</i> infection in cats in Japan

Abstract: Antibodies to Encephalitozoon cuniculi (E. cuniculi) were examined by enzyme-linked immunosorbent assay using E. cuniculi PTP2 recombinant protein from serum samples that had been collected from a total of 295 cats in Japan. Of these samples, 6.1% (18/295) had antibodies against E. cuniculi, which included 6.3% (6/96) of the male cats and 6.0% (12/199) of the female cats. The incidence was slightly higher in feral cats (8.3%, 11/132) compared to domesticated cats (4.3%, 7/163). This suggests the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
8
2
Order By: Relevance
“…1). In contrast, the seroprevalence of FCoV in the current study was higher than observed in Sweden [6], Israel [5], Japan [31], and Australia [25], but lower than in Switzerland [28], Turkey [1,2], China [32], and Brazil [3] (Table 1).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…1). In contrast, the seroprevalence of FCoV in the current study was higher than observed in Sweden [6], Israel [5], Japan [31], and Australia [25], but lower than in Switzerland [28], Turkey [1,2], China [32], and Brazil [3] (Table 1).…”
Section: Discussioncontrasting
confidence: 84%
“…1) was similar to the results of studies from Italy [52,41], Austria [44], Poland [30], Cyprus [46], Israel [5], Brazil [51], and Mexico [42] (Table 2). In the current study, the FeLV prevalence was higher than observed in Ireland [17], Germany [18], Serbia [19], Switzerland [48], USA and Canada [16], Japan [31], Thailand [49], Australia [12], and New Zealand [47], but lower than in Hungary [8], Turkey [1,29], Malaysia [50,9], Iran [43], and China [45] (Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…Modified trichrome stain (MTS) and Gram stain, detected by light microscopy, and calcofluor white stain, detected by ultraviolet light microscopy, are the best stains for detecting spores of E cuniculi in paraffin-embedded tissues. These stains were Stray 17 and feral 23 cats are more likely to be exposed or infected than pet cats.…”
Section: Pcrmentioning
confidence: 95%
“…Various serological investigations with different methodologies and sample sizes were carried out in different countries, with a serological status between 0% and 26.8% [41,[48][49][50][51].…”
Section: Catsmentioning
confidence: 99%
“…Diagnosis of E. cuniculi infections in wild and pet animals is actually based on different strategies, including histopathology, serological testing, such as enzyme-linked immunosorbent assay (ELISA), Western blot, indirect immune fluorescence antibody test (IFAT) and molecular testing, which includes different types of polymerase chain reactions (PCR) [10,50,51,54,[85][86][87]. However, E. cuniculi diagnosis has equally gained an increase in importance in human health, since the microsporidia can live in both immunocompetent and immunocompromised individuals and cause important illness in the latter [77,80,83,88,89].…”
Section: Serological and Molecular Diagnosismentioning
confidence: 99%